Grafting of functional brushes on the surface of 5-Fluorouracil molecularly imprinted polymer particles through RAFT polymerization - Dias, Rolando (2016)
The grafting of functional brushes on the surface of molecularly imprinted polymer (MIP). particles hás been explored in the last few years to synthesize materiais combining high molecular recognition capabilities and stimulation triggered by changes in the surrounding environment [1, 2]. In the present work, MIP particles for 5-fluorouracil (a drug used in câncer treatment) were produced by precipitation polymerization in acetonitrile, using either MAA or HEMA as imprinting fünctional monomers, and m the presence of different kinds of RAFT agents. In a second step, taking advantage of the RAFT groups present in the surface of the particles, different kinds of fiinctional polymer brushes were grafted on the MIPs considering a "grafting from" process in the presence of a RAFT agent.